THE ROLE AND SIGNIFICANCE OF NATIONAL LITERATURE IN SHAPING THE SPIRITUAL DEVELOPMENT OF YOUTH - Axmedjonova Gulnoza Omon qizi (The latest news and research in education, 2025)
This research explores the role and significance of national literature in shaping the spiritual development of youth. It examines how literary texts influence identity formation, moral consciousness, emotional maturity, and cultural understanding among young generations. Drawing on the theories of J. Dewey, L. Vygotsky, M. Bakhtin, E. Erikson, and contemporary scholars, the study demonstrates that national literature serves as a powerful educational and spiritual resource that preserves collective memory and transmits cultural values. The works of classical and modern authors—including Alisher Navoi, Abdulla Qodiriy, Abdulla Oripov, Erkin Vohidov, and other prominent writers—contribute significantly to the development of moral reasoning, empathy, patriotism, and aesthetic taste in youth. The research concludes that national literature remains an essential mechanism for fostering spiritual resilience, cultural identity, and ethical behavior in a globalized society.